(NtEMNOE SERDCEs (NhUDOVESTWENNIE s - (NjOAKIM pALMKWISTs ((NmOSKWAs (NbOMBORAs, 2022)
(N`G {WECII(B- (NKRAJ BOGATYJ LESAMI(B.(Nw KONCE LETA (B2012 (NGODA MILLIONER(B-(NZEMLEWLADELEC jORAN lUNBLAND PROPADAET BEZ WESTI(B.s
Keywords: (NhUDOVESTWENNAQ LITERATURAs